2014
DOI: 10.1111/1751-2980.12168
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute pancreatitis in the elderly Chinese population: A population‐based cross‐sectional study

Abstract: Our study indicated that a higher education level, smoking, alcohol consumption and history of gallstones may be potential risk factors for AP in the elderly in northeast China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Three were duplicate reports based on the same study population, five were not meta-analyzable, and four did not evaluate the correlation between smoking and pancreatitis. As a result, 22 studies [627] were identified in this meta-analysis (Fig 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three were duplicate reports based on the same study population, five were not meta-analyzable, and four did not evaluate the correlation between smoking and pancreatitis. As a result, 22 studies [627] were identified in this meta-analysis (Fig 1). …”
Section: Resultsmentioning
confidence: 99%
“…However, the reported correlations between smoking and pancreatitis risk are inconsistent [627]: some studies showed a positive correlation [68,11–15,17,1924,27], whereas others failed to demonstrate such an association [9,10,16,18,25,26]. This lack of consistency across studies may be due to differences in study populations, differences in methodology or exposure definitions, variations in the quantity of cigarettes consumed, or a shortage of data on confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…The continents or countries in which the studies were conducted were as follows: China (n ¼ 1), the United States (n ¼ 2), and Europe (n ¼ 9). Acute pancreatitis was defined as "upper abdominal pain with a serum amylase level of more than two times the upper limit of normal within 72 h after admission to the hospital, and/or with confirmatory evidence of AP on ultrasonography, computerized tomography" in seven studies [14e17, 23,25,27]. In the remaining five studies, the ascertainment of AP was based on medical claims or diagnostic codes.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…When we were preparing this manuscript, a meta-analysis on the same topic was published, which included only five studies [26]. On reviewing the references, we found that seven studies were not included in that metaanalysis, which reported AP related to alcohol use [14], antihypertensive medications [16,25], multiple etiological factors [24], endoscopic retrograde cholangiopancreatography pancreatitis (ERCP) [23], or reported only of persons who had ever smoked ("ever-smokers") [20,27]. In addition, that meta-analysis did not report doseeresponse relationships or determine whether the etiologic classification of AP (gallstone, alcohol use, drugs, ERCP, etc) influences the association between smoking and the development of AP.…”
mentioning
confidence: 99%
“…In a study of 535 patients diagnosed with CP, 382 (71.4%) reported smoking, yet physicians recorded smoking as a risk factor for only 173 (45.3%). There was also a tendency to do so if the patient was a current smoker, reported elevated levels of smoking and/or had a concurrent alcohol problem (123,124). The importance of smoking as an independent risk factor, particularly for chronic pancreatitis, is becoming vital for interventional purposes in light of new clinical information.…”
Section: Role Of Tobacco In Development Of Pancreatic Disease: Pancrementioning
confidence: 99%